IDENTIFICATION OF DYNAMICS OF ANGLE SPEED SENSOR BLOCKS - Держак, С. В.; Білак, Н. В. (Proceedings of National Aviation University (archive), 2021)
The efficiency of the known algorithm for identification of multidimensional dynamic objects is shown. The results of identification of the block of angular velocity sensors are given.